Simplify:

\(4a \times 3ab+3 a^2 \times 9b\) =

\(4a \times 3ab+3 a^2 \times 9b\) =

`_________`

.Simplify:

\(4a \times 3ab+3 a^2 \times 9b\) =

\(4a \times 3ab+3 a^2 \times 9b\) =

`_________`

.Detailed Explanation

To multiply monomials, multiply the coefficients (the numbers that come before the variables) of each term, add the exponents of like variables, and multiply the different variables together.

\(4a \times 3ab+3 a^2 \times 9b\)

\(= 4 \times 3 \times (a \times ab)+3 \times 9 \times ( a^2b)\)

\(=12 a^2b+27a^2b\)

\(= 39a^2b \)

\(4a \times 3ab+3 a^2 \times 9b\)

\(= 4 \times 3 \times (a \times ab)+3 \times 9 \times ( a^2b)\)

\(=12 a^2b+27a^2b\)

\(= 39a^2b \)